2005
DOI: 10.1111/j.1365-2591.2005.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of vital pulps beneath a metal‐ceramic crown or a bridge retainer

Abstract: The survival of the vital pulp in teeth restored with a single-unit CMC was significantly higher than those serving as an abutment of a fixed-fixed bridge. Maxillary anterior teeth used as bridge abutments had a higher rate of pulpal necrosis than any other tooth types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 23 publications
6
105
2
5
Order By: Relevance
“…This result was also reflected by location of practice, with 82% (100) of high street specialists and 75% (44) of specialist trainees favouring this option (Fig. 18) and 70% (19) of NHS consultants. In contrast, only 33% (four) of honorary consultants were in favour of this option (Fig.…”
Section: Question 3: If Endodontic Retreatment Proves To Be Successfumentioning
confidence: 86%
See 1 more Smart Citation
“…This result was also reflected by location of practice, with 82% (100) of high street specialists and 75% (44) of specialist trainees favouring this option (Fig. 18) and 70% (19) of NHS consultants. In contrast, only 33% (four) of honorary consultants were in favour of this option (Fig.…”
Section: Question 3: If Endodontic Retreatment Proves To Be Successfumentioning
confidence: 86%
“…Endodontic complications of conventional preparations are well documented and may have influenced this decision. [18][19][20] Post discussion opinions among the specialists changed, some becoming more in favour of extraction and prosthetic replacement (restorative dentistry and prosthodontics) and others becoming less in favour (Fig. 20).…”
Section: Effect Of Type Of Specialistmentioning
confidence: 99%
“…1 The use of dental implants avoids the biological complications of, for example, preparing adjacent teeth as bridge abutments. 2,3 Some studies have demonstrated that the occurrence of pulpal necrosis following preparation of abutment teeth for fi xed bridgework can be as high as 30% at ten years. 3 As a result implantology is seen as an increasingly contemporary, integral and important component of the practice of dentistry within the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Probabilities have been reported from 2.6% to as high as 25% that root canal treatment will follow cast crown insertion. [1][2][3][4][5] Kirakozova and Caplan's case-control study here aimed to determine which clinical variables, present at the time when treatment is being planned for a single-cast crown, are predictive of future root canal treatment. This is a question very pertinent to clinical practice.…”
Section: Commentarymentioning
confidence: 99%
“…This amounts to only 1.6% having subsequent root canal treatment to a crowned tooth -less than half the figure reported by others. 1,2 Furthermore, the authors failed to perform a sample size calculation from the start. There are ample data in the literature cited in their study for the authors to have at least attempted to calculate the size of study required to minimise a type-2 error (a false negative).…”
Section: Commentarymentioning
confidence: 99%